Sistem Informasi Kalibrasi Inspection Jig Berbasis Web - Arif Siswandi (Jurnal SIGMA, 2021)
The development of science and technology in this era of globalization has been so rapidly. In line with the problem we face also more complex. Therefore we are required to be able to solve existing problems by utilizing technological sophistication and speed, accuracy and accuracy in providing information so that in carrying out the work can be obtained optimal results. One of them is by utilizing computer technology. The program has several weaknesses in database processing, among others, in the search data less quickly and in the editing process we have to block the data we will edit and then we delete and new editing process can take place. With dreamweaver, php and mysql provide ease in the process of searching data, the process can we set as we want without blocking the data we will edit through the programming language. To secure data security, the difference is the access rights for each user is very important. Because there are some data that it can only be accessed by certain people who are authorized to handle it. Designed program is expected to facilitate the process of data entry, edit data, delete data and search calibration data. Keywords: Technology, Information, Programming, Calibration, Inspection.